Complicated Facial Lacerations: Challenges in the Repair and Management of Complications by a Facial Trauma Team. Issue 1 (March 2023) - De, Moumita; Sagar, Sushma; Dave, Aniket; Kaul, Ruchi Pathak; Singhal, Maneesh
Study Design: This is a descriptive study where we present our experience in managing complicated facial wounds over a period of 1 year at a level 1 trauma centre by a dedicated facial trauma team consisting of a plastic surgeon, a trauma surgeon and a Maxillofacial surgeon. Objective: Facial deformities have profound impact on the social and psychological aspect of a person's life. Hence, management of facial wounds is very crucial. Most of the facial injuries are usually managed by emergency care physician and emergency surgeon. But certain wounds require specialised knowledge and care due to their complicated nature. The objective of this paper is to highlight those special types of wounds and the challenges they pose. It also aims to enumerate the best possible management according to each situation in a protocol-based manner, which will help in decision making by the attending emergency physician/surgeon. Methods: Facial lacerations were designated as "complicated" according to some pre-defined features and pre, intra and post operative data and photographs were collected by interviewing the concerned surgical team. The data were analysed and presented as different clinical scenarios. Results: The cases were broadly grouped under 6 scenarios according to the unique combination of difficulties faced and their specific management. The challenges faced were enumerated and the steps undertaken were also mentioned against them. Lastly, the scenarios were compared with available literature to find out the best possible management in each situation and to present them in a protocol-based manner. Conclusion: Protocol-based management of injuries to the different parts and specialised structures of the face is extremely helpful. Role of a specialised facial trauma team also should be emphasised in complicated facial injuries.